Pengaruh Program Darsul Iḍāf Terhadap Mahāratul Qira'ah Mahasiswi Intensif Semester 1 IDIA Prenduan 2021/2022 - Asmania; Aniq Rasida (KURAS Institute, 2023)
The Darsul Iḍāf program is a language program that has been running for a long time at IDIA Prenduan Sumenep Madura, adapted to the needs of students at the highest level, namely being able to read Arabic texts as stipulated by boarding school. The researchers focused on Mahāratul Qira'ah (reading skills). In this case, we need to know whether the Darsul Iḍāf program has had an impact on intensive Mahāratul Qira'ah second semester IDIA Prenduan for the 2021-2022 academic year. This type of research is quantitative research using simple linear regression with a total of 71 populations as respondents who use observation, questionnaires, and tests as data collection. Linear regression Ha = there is a significant effect between variable X (Darsul Iḍāf program) and Y variable (Mahāratul Qira'ah) while Ho = there is no significant effect between variable X (Darsul Iḍāf program) and variable Y (Mahāratul Qira'ah) . From the results of research with the help of SPSS 22 software. The effect of the Darsul Iḍāf program on Mahāratul Qira'ah intensive 1st semester students of IDIA Prenduan Sumenep Madura 2021-2022 can be seen from the coefficient of determination with a total R square of 0.028 which indicates that the Darsul Iḍāf program has a very large influence weak, namely 28% with conclusions not reaching linearity and can be said to be very low.